ADOPSI NILAI-NILAI AGAMA ISLAM TERHADAP PASAL 496 RUU KUHP TAHUN 2012 - Wiarti, July (UIR Press, 2021)
The current Criminal Code is no longer in accordance with existing developments and is far from fulfilling the values ​​of the Indonesian nation. It is hoped that the 2012 Criminal Code Bill can answer this problem. The issue that is developing is that the Draft Criminal Code will adopt Islamic religious values, prostitution is an act that is also prohibited in the Islamic religion, therefore it should be regulated in the Draft Criminal Code. The problem is whether there is an opportunity for that and what challenges will be faced. If we do adopt Islamic religious values, how can we construct a good formulation regarding prostitution in the future? This research was carried out as a type of normative legal research, namely based on secondary data. The research results that the author found are that there are several challenges, in the form of: Indonesia is not an Islamic country and the population of Indonesia is not only Muslim. theoretical opportunities, namely that law is a fusion of interests, divine law theory, QS. Al-Ma'idah: 15-16, theory in the book